Bentuk Alih Kode dan Campur Kode Dalam Serial Drama Ashghāl Shaqqa Jiddan Episode 9–10 : Kajian Sosiolinguistik (Jurnal Pustaka, 2026)
The practices of code switching and code mixing are part of linguistic dynamics that reflect the culture and social conditions in multilingual societies. In modern communication such as audiovisual media, namely films or drama series, these linguistic events appear as a form of social adjustment or reinforcement of the speaker’s. This study aims to analyze the forms of code switching and code mixing that occur in the dialogues between characters in episodes 9-10 of the drama series Ashghāl Shaqqa Jiddan and to reveal the factors behind their use by employing a qualitative descriptive analytical method based on a sociolinguistic approach. The research data were obtained through listening and recording the dialogues of the characters in the film. Data analysis was conducted using two methods, namely the distribution method to identify the linguistic forms of code switching and code mixing and the frequency method to determine the frequency of their use. The research data was obtained through Simak and Catat technique the speech of the characters in the film. Data analysis was conducted using two methods, namely the Agih method to identify linguistic forms, namely code-switching and code-mixing, and the Padan method to examine the social context behind these linguistic events. The results of the study found 76 data points, namely 48 code-switching data points and 25 code-mixing data points, the use of which was dominated by 4 factors, namely the speaker factor, the speech partner factor, the presence of a third person, and the factor of a change in situation from formal to informal and vice versa.